The impact of Traditional Chinese Medicine utilization on life expectancy and mortality - Jui-Yi Wang; Hsien-Chang Wu; Jing-Shiang Hwang; Wei-Cheng Lo (PLoS ONE, 2025)
Purpose Traditional Chinese Medicine (TCM) is extensively utilized in Asian societies and has shown potential benefits in improving survival rates of patient with specific diseases and anti-aging effects. However, its impact on life expectancy of general population remains relatively unexplored. This study aimed to investigate the impact of TCM utilization on mortality risk and life expectancy in Taiwan. Methods A nationwide longitudinal cohort study was conducted using data from the Taiwan National Health Interview Survey linked with the National Health Insurance Research Database. Cox proportional hazard models were used to calculate the risk of all-cause mortality between frequent TCM users (≥20% of outpatient visits) and non-frequent users (<20%). A rolling extrapolation algorithm was used to estimate lifetime survival functions, and inverse probability of treatment weighting was integrated to adjust for confounding variables. Results The study included 12,176 participants (1,596 frequent TCM users and 10,580 non-frequent TCM users) aged ≥55 years, with a median follow-up duration of 10.49 years. After adjustment for confounding factors, frequent TCM users had a longer life expectancy compared to non-frequent TCM users, with a difference of 1.37 years (95% CI: 0.22–3.32). Higher TCM utilization was associated with reduced mortality risk (HR: 0.89, 95% CI: 0.80–0.99). Results remained consistent across dose-response analysis and time-dependent exposure models. Conclusions This study suggests that higher TCM utilization is associated with longer life expectancy and lower mortality risk among older adults in Taiwan. Further studies are warranted to clarify potential mechanisms and to explore how TCM utilization may complement conventional healthcare in addressing the needs of aging populations.